Salishan and North-Caucasian (Global Journal of Human-Social Science, 2013)
Sa lishan languages are represented in this paper in the following way data used in this paper are taken from the appropriate dictionaries or published word lists Tsamosan Ts Upper Chehalis UP Interior Salish IS Thompson River Salish Th Shuswap Sh Colville-Okanagan CO Moses- Columbian MC Spokane Sp Montana Salish MS Central Salish CS Lushootseed Ls Puget Sechelt Se Squamish Sq Bella Coola Nuxalk BC Nu I am also using occasionally North Wakashan NWk language data as provided by N Lincoln and J C Rath in their North Wakashan Comparative Root List Ottawa 1980 abbreviations Haisla Ha Heiltsuk He Kwakiutl Kwakwala Kw Oowekyala Oo - Note also Wakashan Wk M Makah Nitinat Ni Nootka No North Caucasian NC languages are cited after A North Caucasian Etymological Dictionary by S Nikolaev and S Starostin Asterisk Publishers Moscow 1994 NCED and occasionally also after S St arostin s papers Nostratic and Sino-Cacasian in Explorations in Language Macrofamilies Bochum 1989 42-66 St 89 and On the Hypothesis of a Genetic Connection between the Sino- Tibetan Languages and the Yeniseian and North-Caucasian Languages in Dene-Sino-Caucasian Languages ibid 1991 12-40 St 91 - Note relevant abbreviations North-East Caucasian NEC EC N -West Caucasian NWC WC Sino-Caucasian SC Yeniseian Yen Sino- Tibetan ST Nostratic N